Effects of Corn Stalks Ash as A Substitution Material of Cement Due to the Concrete Strength of Rigid Pavement - Roza Mildawati; Anas Puri; M. Zaky Handayani (Journal of Geoscience, Engineering, Environment, and Technology, 2022)
Cement is an adhesive material for concrete mixtures in addition to water, fine and coarse aggregates. One of the main ingredients of cement is silica (SiO2) which is originated from the earth's crust. Silica is also available in plants such as corn stalks. This research is aimed to utilize the corn stalk ash (CSA) as an alternative substitution for some cement in concrete for the rigid pavement of road construction. According to the Indonesian standard, the flexural tensile strength should be exceeded at least 4.5 MPa. The flexural tensile strength has also a correlation due to compressive strength. The concrete materials consisted of the coarse aggregate (river crushed stone) from Kampar River and Danau Bingkuang sands from Kampar District of Riau Province, and Portland Composite Cement from Semen Padang. The CSA was made by burning the dried corn stalks in a steel cylinder can over 24 hours. The content of CSA was varied by 0%, 5%, 7% and 9%. The compressive strength design of concrete was 31,3 MPa. Testing procedures were based on the Indonesian Standard for concrete. The tested specimens have consisted of cube specimens (150 mm x 150 mm x 150 mm) for compressive tests, and beam specimens (150 mm x 150 mm x 600 mm) for flexural strength tests. All specimens were tested on 28 days-age. The results show that CSA can be used as a partial substitution of cement in concrete. The addition of CSA tends to increase the compressive strength of concrete instead of its flexural tensile strength. The optimum content of CSA was 7% and resulted in an 8.0% and 6.9% increase in compressive and flexural tensile strength due to design respectively. Compressive and flexural tensile strength fulfilled the standard. Flexural tensile strength is obtained by 15% of the compressive strength. Cornstalk ash can be used as a substitution of cement for rigid pavement concrete. It can reduce the utilization of cement and will be potentially cost efficiency.